PEMANFAATAN APLIKASI VIRTUAL LEARNING BERBASIS ANDROID DALAM MENINGKATKAN KUALITAS PEMBELAJARAN - Evan Rosiska (LPPM Universitas Putera Batam, 2019)
The development of science and technology is currently developing so rapidly, the number of the latest innovations in all areas, including education. The development of media-based learning, information and communication technologies such as e-learning or virtual learning which are capable of improving the quality of interactive learning because users are friendly, useful interface features are used quite comfortable for the user so that the user does not get bored, moreover technologies be accessible anywhere and anytime a user is currently learning system, which is still the conventional good already assessed where all the references in the form of books, student worksheets and other learning media must exist, it is certainly not all students get to have all the references, sometimes a certain disaat-saat user forget bring or had to borrow to the other so that it becomes the bottleneck in the process learning. However, the application of information and communication technology as a medium is required in supporting the learning process, the user can perform the work practice or learn the theories related to the learning process in schools is becoming more easy with the utilization of this technology. Using the method of accompaniment in implementing this activity, that accompany the activities from the beginning until the end of this activity, as well as the explanation of the memperikan benefit that can be obtained with the utilization of android-based applications and the expected able to give a positive impact to a better education.